1999
DOI: 10.1016/s0895-7061(99)00119-3
|View full text |Cite
|
Sign up to set email alerts
|

High dietary salt enhances acute depressor responses to metformin

Abstract: The antidiabetic drug metformin lowers blood pressure (BP) more in spontaneously hypertensive rats (SHR) compared with Wistar-Kyoto rats (WKY), and the hypotensive effect is enhanced by high dietary salt. To determine whether enhanced hypotension is secondary to greater decreases in sympathetic nerve activity (SNA), we placed WKY and SHR on normal salt (0.3%), and SHR on high salt (8.0%) for 2 weeks and then measured anesthetized BP and lumbar SNA to metformin (0, 10, 50, and 100 mg/kg, given intravenously). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Clinical studies on the effects of metformin on blood pressure (BP) have shown various findings from decreased to unaltered BP [2, 3]. Metformin has also been reported to lower BP in spontaneously hypertensive rats (SHR) [4]. The protective effect on BP in nondiabetic hypertensives is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies on the effects of metformin on blood pressure (BP) have shown various findings from decreased to unaltered BP [2, 3]. Metformin has also been reported to lower BP in spontaneously hypertensive rats (SHR) [4]. The protective effect on BP in nondiabetic hypertensives is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin sensitizers were described to lead to NO enhancement, reduce oxidative stress and alterations in vascular smooth muscle cells, and inhibit the α-adrenergic tone in patients with diabetes mellitus [ 22 , 30 33 ]. In type-2 diabetes patients, metformin was shown to have an impact on the mesenteric artery by suppressing prostanoids and improving vascular resistance in animal studies [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin sensitizers were described to lead to NO enhancement, reduce oxidative stress and alterations in vascular smooth muscle cells, and inhibit the α-adrenergic tone in patients with diabetes mellitus [22,[30][31][32][33]. In type-2 diabetes patients, metformin was shown to have an impact on the mesenteric artery by suppressing prostanoids and improving vascular resistance in animal studies [31].…”
Section: Introductionmentioning
confidence: 99%